Assessment of DNA-damage repair in breast cancer - Alshareeda, Alaa (2014)
Background: Current evidence indicates that DNA damage response (DDR) is a highly complex process that involves various pathways working in an orchestrated and interwoven manner in response to different types of damage to DNA. Although specific defects of DDR remain to be deciphered in cancer as a general, there is certainly an undeniable relationship between a particular dysfunction of DDR and the phenotype of tumour [1, 2]. It has been demonstrated that familial forms of breast and ovarian cancer are characterised by defects in one of the main mechanisms of DDR homologous recombination (HR) as a result of germline loss-of-function mutations in one of HR modifying genes, such as BRCA1 and BRCA2 [1, 3, 4]. Defects of genes involved in other DDR pathways are also associated with specific types of cancers; for instance hereditary non polyposis colorectal cancer (HNPCC) is strongly associated with specific mutations in the DNA mismatch repair pathway. Several previous studies have demonstrated that impaired DDR play a fundamental role in the pathogenesis and behaviour of breast cancer (BC). However, characterisation of this complex process, the expression and co-expression of the key proteins involved in the various DDR pathways and their prognostic significance in BC remain to be defined. In BC, it is reported that genes involved in DNA double strand breaks (DSB) repair are the most important. Two main pathways are involved in the repair of DNA-DSB; HR and Non Homologous End Joining (NHEJ) [3]. The common characteristics of global DDR are multiple genes induction directly associated with sensing and repair of DNA, arrest of cell cycle, and cell division inhibition. As a result DDR process does not only include genes activation involved in damage sensing as well as repair but additionally genes involved in control of cell-cycle [5]. Despite the fact that DDR may possibly involve activation of several pathways (such as SUMOylation (SUMO)) [6, 7] and many genes are engaged in different overlapping mechanisms, each pathway is characterised by activation and expression of a unique set of genes. This could allow discovering the active or aberrant pathway in a given tumour [1, 4, 5].